2019
DOI: 10.1002/jctb.6129
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the metagenomic link between pre‐treatment method, addition of an inoculum and biomethane yield during anaerobic digestion of water hyacinth (Eichhornia crassipes)

Abstract: BACKGROUND Water hyacinth (Eichhornia crassipes) is a fast growing water weed that threatens the aquatic ecosystem and human activities, hence control of the plant is essential. One such control approach is to harvest and utilize hyacinth as a substrate for anaerobic digestion (AD). Various factors influence AD performance, including substrate pre‐treatment and microbial community composition, amongst others. This study was aimed at establishing the link between method of substrate pre‐treatment, microbial div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…The growth of the microbial community is affected by reaction parameters including pH, temperature, and nutrient balance, such as the C/N ratio. Thus, the microbiome changed along with the alternations of these parameters during AD [ 133 , 134 ]. To further enhance sustainability, WH is often co-digested with other plant biomass, animal dung and other wastes [ 135 , 136 ].…”
Section: Main Mechanisms Underlying Wh Utilization In Environmental S...mentioning
confidence: 99%
“…The growth of the microbial community is affected by reaction parameters including pH, temperature, and nutrient balance, such as the C/N ratio. Thus, the microbiome changed along with the alternations of these parameters during AD [ 133 , 134 ]. To further enhance sustainability, WH is often co-digested with other plant biomass, animal dung and other wastes [ 135 , 136 ].…”
Section: Main Mechanisms Underlying Wh Utilization In Environmental S...mentioning
confidence: 99%
“…However, Photong and Wongthanate [ 108 ] demonstrated that cumulative methane production is higher when the process occurs at a thermophilic temperature of 55 °C (230 mL/g COD methane produced), compared to a mesophilic temperature (methane production at 110 mL/g COD ). Methane yield rises at higher temperatures have been linked to lower enzyme activation energy, higher hydrogen production, stable consortia population and increased methane cumulative production [ 109 , 110 , 111 ]. Overall, many processes involved in anaerobic digestion are biochemical and highly dependent on the reaction rates of the enzymes involved [ 106 ].…”
Section: Prospects For Water Hyacinthmentioning
confidence: 99%
“…Inoculum starter is a prerequisite at the commencement of the digestion process; however, subsequent processes may occur without the addition of inoculum. Nevertheless, the absence of inoculum causes more dynamic variations in the microbial community, leading to increased lag time and lower biomethane concentration, regardless of pre-treatment [ 111 ]. From the perspective of rural communities planning to adopt the AD approach to treat their agricultural or municipal waste, the use of inoculum is an interesting opportunity, as locals could use any available inoculum source from their economic activities, such as waste from cow-herding, poultry farming or fishing.…”
Section: Prospects For Water Hyacinthmentioning
confidence: 99%
“…In addition to the aforementioned qualities, low lignin content of water hyacinth and its possession of plants’ essential nutrients make it a suitable substrate for efficient production of biogas and soil ameliorant (Njogu et al 2021 ; Barua and Kalamdhad 2019 ). The use of water hyacinth to generate biogas is an eco-friendly and innovative means of managing this intrusive aquatic weed (Roopnarain et al 2019 ). Water hyacinth is a menace in the aquatic environments as its rapid proliferation hinders many biological and socioeconomic activities where they are resident (Honlah et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of water hyacinth as a potential inoculum to enhance biogas production is yet to be investigated. A study that reported that biogas-producing microorganisms are innately linked to water hyacinth harvested from the Hartbeespoort dam in South Africa motivated the investigation into the potential of these microorganisms as an inoculum (Roopnarain et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%